Charge‐Conversion Strategies for Nucleic Acid Delivery. (31st March 2021) - Dutta, Kingshuk; Das, Ritam; Medeiros, Jewel; Kanjilal, Pintu; Thayumanavan, S.
Abstract: Nucleic acids are considered as one of the most potent therapeutic modalities, as their roles go beyond storing genetic information and chemical energy or as signal transducers. Attenuation or expression of desired genes through nucleic acids have profound implications in gene therapy, gene editing, and even in vaccine development. Although nucleic acid therapeutics bring in overwhelming possibilities toward the development of molecular medicines, there are significant loopholes in their effective clinical translation. One of the major pitfalls lies in the traditional design concepts of nucleic acid drug carriers, namely, cationic charge induced cytotoxicity. Targeting this bottleneck, several innovative carrier designs have been proposed accommodating charge‐conversion approaches, whereby built‐in functionalities convert from cationic to neutral or anionic, or even from anionic to cationic enabling the carrier to overcome several critical barriers for therapeutics delivery, such as serum deactivation, instability in circulation, low transfection, and poor endosomal escape. This review will critically analyze various molecular designs of charge‐converting nanocarriers in a classified approach for the successful delivery of nucleic acids. Accompanied by the narrative on recent clinical nucleic acid candidates, the review concludes with a discussion on the pitfalls and scope of these emerging approaches. Abstract : Nucleic acids have emerged as one of the most potential biologic drugs that can address many challenging disease threats affecting global health. This review will critically analyze the major developments in the charge‐conversion strategies for effective encapsulation and delivery of nucleic acid therapeutics.